2023
DOI: 10.4082/kjfm.22.0022
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Bone Mineral Density and Oxidative Stress Biomarkers in Postmenopausal Women

Abstract: Background: Oxidative stress plays an essential role in bone health among postmenopausal women. This study aimed to compare the oxidative stress biomarkers among postmenopausal women aged 50–65 years with normal bone mineral density, osteopenia, and osteoporosis.Methods: In this observational study, 120 women with normal bone mineral density, 82 with osteopenia, and 86 with osteoporosis were selected based on the densitometry data obtained from the dual-energy X-ray absorptiometry method. The serum total antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…The expression and activity of SOD have a profound influence and response on vascular cells experiencing acute and chronic oxidative stress ( Wahjuni, 2015 ). Research by Sanaz et al concluded that higher SOD activity in postmenopausal women was associated with a significantly lower risk of osteoporosis ( Malekian et al, 2023 ). Based on data from the Indonesian Ministry of Health, the number of osteoporosis patients in Indonesia is much larger and is the country with the 2nd largest osteoporosis sufferer after China, with a population over 60 years old at higher risk of osteoporosis ( Leopoldini et al, 2011 ; Dirjen Pelayanan Kesehatan, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The expression and activity of SOD have a profound influence and response on vascular cells experiencing acute and chronic oxidative stress ( Wahjuni, 2015 ). Research by Sanaz et al concluded that higher SOD activity in postmenopausal women was associated with a significantly lower risk of osteoporosis ( Malekian et al, 2023 ). Based on data from the Indonesian Ministry of Health, the number of osteoporosis patients in Indonesia is much larger and is the country with the 2nd largest osteoporosis sufferer after China, with a population over 60 years old at higher risk of osteoporosis ( Leopoldini et al, 2011 ; Dirjen Pelayanan Kesehatan, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Primary care physicians should focus on establishing prevention and treatment strategies for women's overall health, including contraception, pregnancy, childbirth, and menopause management. [7][8][9] Throughout this process, the socio-cultural environment affecting women's health should also be carefully considered.…”
mentioning
confidence: 99%